2010
DOI: 10.1002/hlca.200900233
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Membrane Interaction on Immobilized Liposome Chromatography Compared to Immobilized Artificial Membrane (IAM), Liposome/Water, and Octan‐1‐ol/Water Systems

Abstract: The objective of this study was to investigate drug -membrane interaction by immobilized liposome chromatography (ILC; expressed as lipophilicity index log K s ) and the comparison with lipophilicity indices obtained by liposome/H 2 O, octan-1-ol/H 2 O, and immobilized artificial membrane (IAM) systems. A set of structurally diverse monofunctional compounds and drugs (nonsteroidal antiinflammatory drugs and b-blockers) were selected in this study. This set of solutes consists of basic or acidic functionalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…No significant correlation was found between log K s and log D from liposome/water partitioning system, log k IAMw or log D oct for structurally unrelated compounds (104,108).…”
Section: Immobilized Liposome Chromatography (Ilc)mentioning
confidence: 61%
“…No significant correlation was found between log K s and log D from liposome/water partitioning system, log k IAMw or log D oct for structurally unrelated compounds (104,108).…”
Section: Immobilized Liposome Chromatography (Ilc)mentioning
confidence: 61%
“…uptake of the drug through the cell membrane) is the rst step of the drug's action. 175,181,183 CAPILLARY ELECTROPHORESIS. CE is an analytical technique that separates ions based on their electrophoretic mobility with the use of an applied voltage.…”
Section: Analytical Sciencementioning
confidence: 99%
“…But the total coating amounts were only slightly different, 121.85 and 112.21 μmol PC were coated on PCZM and PCS, respectively (see Table 1). The retention time of benzene and toluene on PCZM was longer than that on PCS, but the difference was slight, which also illustrated that the total amount of PC coated on two chromatography columns was slightly different because the retention time of the solute was in proportion to the amount of coated PC 11.…”
Section: Resultsmentioning
confidence: 94%
“…When the artificial PC membrane chromatography was used for screening drugs, the strong lipophilic solutes had long retention times or were not eluted out at all by using pure buffer (no organic solvent) as the mobile phase, which limited its application. In order to resolve this problem, Beigi and Lundahl tried to use a small column to reduce the amount of immobilized liposome, which would result in the decrease in the retention time of strong lipophilic solutes 11. Compared with the results on the normal size columns, it is shown that this method was successful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation